PELAKSANAAN PILKADA SERENTAK YANG DEMOKRATIS, DAMAI DAN BERMARTABAT - Achmad Arifulloh (Jurnal Pembaharuan Hukum, 2016)
In practice, the election of regional heads sparked conflicts, among others triggered by the problems of voter data administration, the neutrality of election organizers, and the lack of compliance of local elections and political parties to the prevailing regulations. This study uses a reflexive qualitative research method, which is to reflect on the simultaneous regional head election and its relation to the effort to build democracy in the local government and politics and ensure the presence of common good in society. The problem is how the simultaneous election of regional heads as the national political agenda towards democratization can proceed substantially and not merely procedural rituals.This paper will describe the Implementation of Democratic, Peaceful and Dignified Democratic Head election in realizing fair and open competition in the regional head elections simultaneously.The results of the study indicate that the election of democratic, constitutional, peaceful and dignified regional head is the election of the regional head which is transparent, accountable, credible and participative in implementation process, and the result is acceptable to all parties, thus ensuring the presence of common good in the community.